PIDANA HUKUMAN MATI DI INDONESIA DALAM PERSPEKTIF ETIKA DEONTOLOGI - Rohmatul Izad (Fakultas Syariah IAIN Ponorogo, 2019)
AbstractDiscourse about capital punishment is a discourse that often causes polemics. Problems that underlie the problem of capital punishment do not only occur in the realm of law, but also the realm of thought outside. The problem that often becomes polemic is whether the death penalty for serious criminals will have a deterrent effect for anyone not to commit the same crime, is a life not the most substantial right of life for humans, and capital punishment is often considered contrary to human rights. This study specifically examines capital punishment in Indonesia in terms of deontological ethics theory, which looks at the issue of capital punishment from the perspective of ethical values that start with acts of kindness based on duties and obligations. This study analyzes the polemic of capital punishment, both pros, and cons, as well as tracing the roots of morality in the practice of capital punishment, so this research can make a new contribution through the perspective of ethical deontology in viewing ethical aspects in the practice of capital punishment. On this basis, this research uses a descriptive-interpretative approach. Researchers critically dissect how the root of the formation of the death penalty in Indonesia, by carefully reviewing it from the perspective of ethical deontology.Keywords: Death Penalty, Deontology Ethics, Human Rights. AbstrakWacana tentang pidana hukuman mati merupakan wacana yang banyak menimbulkan polemik. Problem yang mendasari persoalan pidana hukuman mati tidak hanya terjadi pada ranah hukum, tetapi juga dalam ranah pemikiran secara luar. Masalah yang sering menjadi polemik adalah apakah hukuman mati bagi para pelaku pidana berat akan menimbulkan efek jera bagi siapapun untuk tidak melakukan tindak kejahatan yang sama, bukankah nyawa adalah hak hidup paling substansial bagi manusia, dan hukuman mati seringkali dianggap bertentangan dengan hak asasi manusia. Penelitian ini secara khusus mengkaji tentang pidana hukuman mati di Indonesia ditinjau dari sudut teori etika deontologi, yakni melihat persoalan pidana mati dari perspektif nilai-nilai etis yang bertitik tolak pada tindakan kebaikan berdasarkan tugas dan kewajiban. Penelitian ini menganalisis tentang polemik hukuman mati, baik yang pro dan kontra, maupun menelusuri akar-akar moralitas dalam praktik pidana hukuman mati, kiranya penelitian ini dapat memberikan kontribusi baru melalui cara pandang etika deontologi dalam melihat sisi-sisi etis dalam praktik pidana hukuman mati. Atas dasar tersebut, penelitian ini menggunakan pendekatan deksriptif-interpretatif. Peneliti membedah secara kritis bagaimana akar terbentuknya hukuman mati di Indonesia, dengan secara cermat melakukan peninjauan dalam perspektif etika deontologi.